2020
DOI: 10.1002/tpg2.20031
|View full text |Cite
|
Sign up to set email alerts
|

Identification of regions under selection and loci controlling agronomic traits in a soft red winter wheat population

Abstract: Comprehensive information of a breeding population is a necessity to design promising crosses. This study was conducted to characterize a soft red winter wheat breeding population that was subject of intensive germplasm introductions and introgression from exotic germplasm. We used genome-wide markers and phenotypic assessment to identify signatures of selection and loci controlling agronomic traits in a soft red winter wheat population. The study of linkage disequilibrium (LD) revealed that the extent of LD a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 92 publications
(141 reference statements)
1
9
0
Order By: Relevance
“…However, chromosomes 1A, 1B, 6A, and 6B showed widespread variation across genomic regions suggesting that the influence of intense selection and domestication pressures on these chromosomes is minimal. The distal regions of all chromosomes showed higher genomic variation than the proximal regions and indicated the occurrence of balancing selections in these regions, in agreement with previous research in wheat ( Zhou et al., 2018 ; Liu et al., 2019 ; Maccaferri et al., 2019 ; Gaire et al., 2020 ; Mazzucotelli et al., 2020 ). Zhou et al.…”
Section: Discussionsupporting
confidence: 92%
“…However, chromosomes 1A, 1B, 6A, and 6B showed widespread variation across genomic regions suggesting that the influence of intense selection and domestication pressures on these chromosomes is minimal. The distal regions of all chromosomes showed higher genomic variation than the proximal regions and indicated the occurrence of balancing selections in these regions, in agreement with previous research in wheat ( Zhou et al., 2018 ; Liu et al., 2019 ; Maccaferri et al., 2019 ; Gaire et al., 2020 ; Mazzucotelli et al., 2020 ). Zhou et al.…”
Section: Discussionsupporting
confidence: 92%
“…Approximately 32 or 47% of the identified genomic regions under selection overlapped with frequently or rarely occurring large chromosomal modifications, respectively (Table S5), i.e., introgressions from wheat wild relatives identified by coverage analysis (Keilwagen et al., 2019; Keilwagen et al., 2022). The connection between genomic regions under selection and genomic regions carrying introgressions has so far only been described for the 2B/2G introgression from Triticum timopheevii (Cavanagh et al., 2013; Gaire et al., 2020). To the best of our knowledge, besides the 2B/2G introgression, only for the frequently occurring introgressions on chromosome 2A and 2D information about the origin and the underlying genes are available (Table S5).…”
Section: Resultsmentioning
confidence: 99%
“…In previous studies, genomic regions under selection were identified in diverse wheat collections using different statistical approaches (Afzal et al., 2019; Cavanagh et al., 2013; Cheng et al., 2019; Fradgley et al., 2019; Gao et al., 2017; Gaire et al., 2020; Jordan et al., 2015; Liu et al., 2019; N'Diaye et al., 2018; Pont et al., 2019). Generally, it is difficult to compare results among studies that have used different marker systems, genotype collections, and maps (genetic versus physical).…”
Section: Methodsmentioning
confidence: 99%
“…The recurrent use of a small population of modern commercial cultivars in breeding programs has been suggested to have exacerbated this problem ( Mikel et al, 2010 ; Keilwagen et al, 2014 ). Exotic or under-utilized germplasm has emerged as a desirable source of novel genetic variation that could help breeders overcome these concerns ( Sneller et al, 2005 ; Fox et al, 2015 ; Wang et al, 2017 ; Kofsky et al, 2018 ; Gaire et al, 2020 ; Kilian et al, 2020 ). However, the use of exotic germplasm has yet to be widely adopted despite a growing body of literature in support of the use of under-utilized germplasm, as well as occurrences of positive contributions from exotic or under-utilized germplasm sources ( Palomeque et al, 2009a , 2009b , 2010 ; Kim et al, 2011 ; Rossi et al, 2013 ; Akpertey et al, 2014 ; Bellaloui et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%